A Systematic Review and Meta-analysis on the Efficacy of Intravesical Therapy for Bladder Pain Syndrome/Interstitial Cystitis. Issue 11 (November 2016) - Barua, Jayanta M.; Arance, Ignacio; Angulo, Javier C.; Riedl, Claus R.
Abstract : (Abstracted from Int Urogynecol J 2016;27:1137–1147) Although the precise pathophysiology of bladder pain syndrome/interstitial cystitis (BPS/IC) is unclear, the underlying mechanism appears related to a defect in the urine-tissue barrier (the bladder's protective mucous lining of glycosaminoglycans [GAG]). This defect has been documented in a subset of BPS/IC patients, and a favorable response to GAG-restoring agents has been reported.